(Social) Media Logics and Visualizing Climate Change: 10 Years of #climatechange Images on Twitter. (March 2023) - Mooseder, Angelina; Brantner, Cornelia; Zamith, Rodrigo; Pfeffer, Jürgen
Images have become a key vehicle for communicating climate change, especially in a visually oriented social media ecosystem. However, few studies have examined the ways in which climate change is visually communicated on those platforms. This study addresses that gap by examining more than 2 million images appearing alongside tweets containing #climatechange, identifying the types of images different stakeholders share and the amount of engagement those images elicit. It highlights differences in the image types that are published frequently (e.g., textual visualizations), the image types that users prefer to engage with (e.g., protest images), and the impact of bots and a cyclical communication pattern keyed to focusing events. These findings are then evaluated through a conceptual framework of media logics, which helps highlight some of the distinctions between (news) media logic and social media logic—and their emerging hybridization—within the context of climate change communication.